Labral gland in soldiers of the neotropical termite Cornitermes cumulans (Isoptera: Termitidae: Syntermitinae) - Costa-Leonardo, Ana Maria [UNESP]; Haifig, Ives [UNESP] (Elsevier B.V., 2014)
Cornitermes cumulans is a termite species of the subfamily Syntermitinae with a nasute mandibulate soldier caste, members of which are morphologically equipped with structures and organs specialized for the defence of the colony. We investigated the labrum of soldiers of C cumulans and described the labral gland, an exocrine structure present in this appendage. The labrum of C. cumulans soldiers presented two distinct regions, the hyaline tip and the proximal region connected to the head. The hyaline tip exhibited a thick cuticle composed of a loose endocuticle involving an epithelium of class 1 cells, which synthesize the glandular product into a subcuticular space that function as a reservoir prior to release the final secretion. The proximal region of the labrum had an epithelium composed of class 1 and class 3 cells, which released the secretion onto both ventral and dorsal surfaces. The ultrastructure showed abundant smooth endoplasmic reticulum and glycogen in the class 1 cells, whereas the class 3 cells had many electron-lucent vesicles that varied in size. We associated the labral gland with the production of toxic substances that may act inside enemy wounds made by the soldiers' mandibles. Other possible functions for the labral secretion are also discussed. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Class 1 cells; Class 3 cells; Labrum; Scanning microscopy; Ultrastructure